Evaluation of Antimicrobial and Antioxidant Activities of Endophytic Penicillium and Aspergillus Species Isolated from Curcuma caesia Roxb. (Zingiberaceae), a Medicinal Plant of Odisha, India - Soumya Priyadarsini; Deepa Biswas; Subhashree Rath; H.N. Thatoi (The Bioscan, 2025)
In addition to being important sources of bioactive chemicals, medicinal plants are essential for the development of new therapeutic medicines. The capacity of endophytic fungus linked to medicinal plants to create a variety of secondary metabolites with important biological functions has drawn more attention. The antibacterial and antioxidant properties of endophytic fungi isolated from the medicinal plant Curcuma caesia Roxb. (family Zingiberaceae) were examined in this work. Based on morphological traits, three endophytic fungal isolates from the plant's rhizomes were identified as Aspergillus oryzae, Penicillium citrinum, and Aspergillus niger. This identification was verified by 18S rRNA sequencing using ITS markers. The isolates' antibacterial activity against four human pathogenic bacteria Bacillus subtilis, Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa was first assessed using the agar block method. P. citrinum produced inhibition zones up to 3.5 cm against the investigated pathogens, demonstrating the greatest antibacterial activity among the isolates. The disc diffusion method was used for secondary screening with ethyl acetate extracts. DPPH and DMPD radical scavenging tests were used to measure antioxidant activity. While A. oryzae demonstrated the highest activity in the DMPD testing (59.56%), P. citrinum demonstrated the highest DPPH antioxidant activity (78.61%). Additionally, all isolates showed enzymatic activity, such as tyrosinase, protease, and amylase. These results suggest that C. caesia endophytic fungus could be useful sources of bioactive compounds with possible medical uses.